Auto-adjusting and Advanced Positive Airway Pressure Therapeutic Modalities - Ryden, Armand; Bando, Joanne M.; Aysola, Ravi S. (Seminars in Respiratory and Critical Care Medicine, 2014)
Continuous positive airway pressure (CPAP) therapy is the first-line treatment for obstructive sleep apnea (OSA). Although the gold standard for the treatment of OSA, CPAP may not be the optimal modality to treat more complex sleep disordered breathing such as Cheyne–Stokes respirations, opioid-induced central apnea, and complex sleep disordered breathing related to chronic hypoventilation syndromes (obesity–hypoventilation syndrome, restrictive thoracic disease due to neuromuscular or thoracic cage disease, chronic obstructive pulmonary disease). Newer generation auto-adjusting PAP devices are increasingly being used to treat OSA. Advanced positive airway pressure modalities have been developed in an effort to improve treatment of the more complex sleep disordered breathing syndromes including automated servo ventilation and volume-targeted pressure-limited ventilation. This article is intended to provide the clinician reader with a description of newer PAP modalities, a review of evidence-supported indications for use, as well as to provide a framework for managing patients with advanced positive airway pressure therapy.
Keywords: positive airway pressure therapy; auto-adjusting; servo ventilation; sleep disordered breathing